2002
DOI: 10.1046/j.1365-2249.2002.01856.x
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of phosphodiesterase 7 in human T cell function: comparative effects of two phosphodiesterase inhibitors

Abstract: SUMMARY Even though the existence of phosphodiesterase (PDE) 7 in T cells has been proved, the lack of a selective PDE7 inhibitor has confounded an accurate assessment of PDE7 function in such cells. In order to elucidate the role of PDE7 in human T cell function, the effects of two PDE inhibitors on PDE7A activity, cytokine synthesis, proliferation and CD25 expression of human peripheral blood mononuclear cells (PBMC) were determined. Recombinant human PDE7A was obtained and subjected to cyclic AMP‐hydrolysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 51 publications
2
37
0
Order By: Relevance
“…These observations might be relevant in the context of T-cell activation, which involves PKC signalling, and requires induction of hPDE7A [12]. Moreover, the use of selective inhibitors has revealed the general contribution of hPDE7 to the regulation of T-cell functions [32]. hPDE7A1 and hPDE7A3 might share a common promoter hPDE7A isoforms are differentially expressed in some tissues.…”
Section: In Jurkat T-cells a 29-kb Fragment Of The Hpde7a1 5 -Flankmentioning
confidence: 91%
See 1 more Smart Citation
“…These observations might be relevant in the context of T-cell activation, which involves PKC signalling, and requires induction of hPDE7A [12]. Moreover, the use of selective inhibitors has revealed the general contribution of hPDE7 to the regulation of T-cell functions [32]. hPDE7A1 and hPDE7A3 might share a common promoter hPDE7A isoforms are differentially expressed in some tissues.…”
Section: In Jurkat T-cells a 29-kb Fragment Of The Hpde7a1 5 -Flankmentioning
confidence: 91%
“…Genomic DNA (30 µg) was digested with BamHI, BamHI + HpaII or BamHI + MspI. Digested DNAs were then analysed by electrophoresis on 0.8 % agarose/ Tris/borate/ EDTA gels, transferred to nylon and hybridized with a randomly labelled 32 P probe spanning nucleotides − 1425 to − 290 of the hPDE7A 5 -flanking region.…”
Section: Southern-blot Analysismentioning
confidence: 99%
“…PDE7 antisense oligonucleotides inhibited proliferation and IL-2 production in a PKA-dependent manner (Li et al, 1999). With PDE4/PDE7 dual inhibitors, it was also reported that PDE7 may play a role in Tlymphocyte activation (Nakata et al, 2002). However, in another study the PDE7 selective inhibitor BRL 50481 had only a small effect on CD8 ϩ lymphocyte cell proliferation and only in the context of concomitant PDE4 inhibition (Smith et al, 2004).…”
Section: Localizationmentioning
confidence: 96%
“…The functions of the enzyme remain largely to be determined. However, PDE7 mRNA and protein are expressed in a wide variety of immune cells (Smith et al, 2003), and evidence suggests that PDE7 may play a role in T-lymphocyte activation (Li et al, 1999;Glavas et al, 2001;Nakata et al, 2002;Smith et al, 2004). Given the high value of pharmacological targets that are involved in inflammation, a great deal of effort has been expended in developing PDE7 selective inhibitors.…”
Section: Overviewmentioning
confidence: 99%
“…Both PDE7 inhibitors, used at concentrations below the IC 50 for inhibition of other PDEs, selectively induced apoptosis of CLL cells (Fig. 3A) (16)(17)(18).…”
Section: Cll Cells Are More Sensitive To the Cytotoxic Effects Of Pdementioning
confidence: 99%